Development of A Neuroscreen-1 Cell-Based In Vitro Parkinson’s Disease Model and Discovery of PLT50: Neuroprotective Effects and Molecular Mechanisms - Pin Fen, Chua (Universiti Malaysia Sarawak, 2025)
Parkinson’s disease (PD) is the second most common neurodegenerative disease and the fastest-growing neurological disorder in the world. To date, no disease-modifying drug is approved clinically for treating PD. The complex pathology of PD remains a challenge in PD drug discovery. Hence, a cellular model of PD that can replicate such pathological features is useful for advancing our understanding of the underlying pathological mechanisms, identifying therapeutic targets, and screening for drug candidates. Phenotypic drug screening using an in vitro cellular model is an important approach in PD drug discovery. As most central nervous system (CNS) drugs come from natural products, this is an important source of potential drugs for PD. This study aimed to develop and optimise an in vitro Neuroscreen-1 (NS-1) cell-based PD model to screen potential compounds from plants and investigate their molecular mechanisms. This in vitro PD model used the neurotoxin 6-hydroxydopamine (6-OHDA) to mimic the pathogenesis of PD. The model's optimisation includes the cell density and cell confluency of NS-1 cells and the concentration of 6-OHDA. Our optimisation experiments showed that 10 µM 6-OHDA is sufficient to induce cell death for screening compounds via cell viability readout as compared to reported concentrations of 20-300 µM of 6-OHDA. PD involves the progressive loss of dopaminergic neurons in the substantia nigra and the accumulation of Lewy bodies, which contains α-syn aggregates. Pathological hallmarks such as dopamine secretion, α-syn expression and neuronal apoptosis were assessed to show the proof of concept of the model. We showed that the model replicated the pathology of PD by showing cells dying from apoptosis and reducing dopamine secretion. Although NS-1 cell line is an effective model for studying dopaminergic neuronal death via apoptosis, it is not a suitable model for α-synucleinopathy. We demonstrated that HEK293T cell line is a suitable cellular model for investigating endogenous α-synucleinopathy as 6-OHDA increased the expression of pathological/phosphorylated α-syn. The model was validated by screening plant-derived neuroprotectants: alpha-mangostin (α-MG), beta-mangostin (β-MG) and gamma-mangostin (γ-MG). With the validated model, we screened compounds from three plants genera: Callophyllum, Uncaria and Aglaia. Screening compounds from the plant genus Callophyllum showed four xanthones - ananixanthone, thwaitesixanthone, brasixanthone B and trapezifolixanthone to be neuroprotective in the in vitro PD model. This is the first report of thwaitesixanthone and brasixanthone B possessing neuroprotective properties. Three compounds (catechin/epicatechin) - EF3, SPB, and SP1 from genus Uncaria also showed neuroprotective activity in PD. A novel compound, PLT50 from genus Aglaia was found to have greatest neuroprotective activity. Therefore, it was selected for further investigation of its neuroprotective mechanisms. PLT50 reduced mitochondrial dysfunction by increasing mitochondrial membrane potential (MMP) and lowering the oxidative stress from 6-OHDA. PLT50 also increased pAKT as a survival signalling pathway for PD. Receptor-mediated mechanisms involving cannabinoid 1 receptor, adenosine A2A receptor, 5-HT1A receptor and CXCR4 receptor were investigated. Results showed that PLT50’s anti-apoptotic effect was abolished when treated with 5-HT1A receptor and CXCR4 receptor antagonist, suggesting the receptors were involved in the protective mechanism. Fluorescent-labelled ligand competitive assay confirmed the binding of PLT50 to the 5-HT1A and CXCR4 receptor. PLT50 is potentially an agonist for the two receptors. In summary, this study established and optimised a cellular PD model using NS-1 cells and provide the first report of HEK293T cells as a model for α-synucleinopathy. Compound PLT50 from genus Aglaia is potentially a PD disease-modifying drug involving two receptors, 5-HT1A and CXCR4.